Driver rehabilitation and community mobility : principles and practice - Pellerito, Joseph Michael; ScienceDirect eBooks (St. Louis, Mo. ; London : Elsevier Mosby, 2005)
An emerging practice area for occupational therapists, adapted driving services is becoming increasingly popular as technology and demographics influence demand for these services. Not only does this text provide the tools necessary to effectively evaluate and rehabilitate disabled and aging drivers, it also prepares readers to enter the field by utilizing true-to-life case studies and evidence-based content. An Adapted Driving Decision Guide that allows therapists to determine a client's transportation need and driving abilityStudy questions in every chapter to enhance student comprehensionNecessary client resources such as downloadable forms, handouts, and reports contained in an interactive CD-ROMComprehensive coverage of people with disabilities across the lifespanGuidance on how to set up a driver rehabilitation program with key information on program and professional developmentSeven appendices enabling students to quickly access important resourcesCurrent information for students and faculty with weblinks on adaptive equipment, vehicle modification, and regulationsDetailed artwork and illustrations on testing, traffic safety principles, vehicle modifications, and adaptive driving equipmentExpert contributions from the foremost authorities in the field of driver rehabilitation.
Part I: Introduction, History, and the Driver Rehabilitation Team -- 1. Introduction and Overview -- 2.Community Mobility and Driving: An Historical Perspective -- 3. Driving Across the Lifespan: Rites of Passage in American Culture -- 4. Driver Rehabilitation: Yesterday and Today -- 5. Roles of the Driver Rehabilitation Team: From Referral to Follow-up -- Part II: Measuring Driving Potential before Hitting the road -- 6. The Adapted Driving Decision Guide -- 7. The Driver Rehabilitation Clinical Evaluation -- Section A: Vision and Hearing Conditions -- Section B: Neurologic Conditions -- Section C: Orthopedic Conditions -- Section D: Psychosocial Conditions -- 6. Neuropsychology and Driving: Predicting Driver Readiness -- 7. Medications, Disabilities, and Driving -- 8. The Impact of Positioning and Mobility Devices on transportation -- 9. Driving Simulators: Bridging the Divide between the Clinical and On-the-road Evaluations -- Part III: Measuring and Improving Driving Performance -- 12. Adaptive Equipment and Vehicle Configuration -- 13. On-the-road Evaluation of Driving Performance -- Section A: General Principles -- Section B: Vision and Hearing Impairments -- Section C: Psychosocial Impairments -- 14. On-the-Road Driver Rehabilitation and Training -- 15. Documenting the Clinical Evaluation and Driving Performance Outcomes -- 16. Funding for Driver Rehabilitation Services and Equipment -- Part IV. Environmental Factors Impacting Drivers, Passengers, and Pedestrians -- 17. Universal Design and the Automobile -- 18. Wheelchairs, Wheelchair Tie-downs, and Occupant Restraints for Improved Safety and Crash Protection -- 19. Intelligent Transport Systems -- 20. Designing the External Environment for Safety and Success -- 21. Driver Rehabilitation for Recreation and Leisure -- 22. Driving Alternatives: Urban Planning, Mass Transit, Public and Private Transportation -- Part V. Professional Ethics and Evidenced-Based Driver Rehabilitation Practice -- 23. Legal and Professional Ethics in Driver Rehabilitation -- 24. Research and Evidenced-Based Practice in Driver Rehabilitation -- 25. Driving Under Stress, Driving After Rehabilitation: Next Generation Neuroimaging and Watching People Think and Improve Performance -- Part VI. Professional and Program Development in a Rapidly Evolving Field -- 26. Driver Rehabilitation Program Development -- 27. Professional Development for the Driver Rehabilitation Specialist -- 28. Driver Rehabilitation on the Horizon -- Glossary of Terms -- Appendices -- Appendix A. Manufacturers of Driver Rehabilitation Products -- Appendix B. Driver Rehabilitation Service Providers -- Appendix C. State Licensing Requirements and Reporting Laws -- Appendix D. CPT codes -- Appendix E. Professional Development for the Driver Rehabilitation Specialist -- Appendix F. Educational Materials for Clients and Caregivers -- Appendix G. Occupational Therapy Practice Framework.
Print version record.
Includes bibliographical references and index.
Elsevier
Keywords: Automobile drivers -- Rehabilitation; Automobile drivers -- Evaluation; Automobile drivers -- Ability testing; Automobile Driving; Disabled Persons -- rehabilitation; Automobiles; Eligibility Determination -- methods; Equipment Design -- instrumentation; Ergonomics -- instrumentation; Transportation -- methods; Wheelchairs; Automobile drivers -- Evaluation; Automobile drivers -- Rehabilitation; Electronic books